Comparative Analysis of The Modern Edition of The Work “Isharat Аl-Marаm” With The Manuscripts - Saidmuhammadkhon D. Muhibullayev (Penerbit Jurnal Indonesia, 2024)
This article is devoted to the comparative analysis of the modern editions and manuscripts of the work